Physicians’ attitudes against clinical practice guidelines on the use of guidelines: A scale development study - ÇELİK, YUSUF (My University, 2022)
This study aims at developing scale measuring attitudes of physicians against clinical practice guidelines (CPGs) and investigate whether the attitude of physicians against CPGs has an effect on the use of CPGs. ‘The Physicians’ Attitudes Against CPGs and The Use of CPGs’ was developed and used to collect data from the physicians working in a public education and research hospital. Physicians’ attitudes that were constructed as an upper latent variable were significant, positive and highly effective on the use of CPGs. Furthermore, the attitude upper latent variable explained 30% of the variance in the observed variable for the use of CPGs. The attitude upper latent variable was affected significantly, positively and at a remarkably high level by positive attitude latent variable while it was affected significantly, negatively and at a remarkably high level by negative attitude latent variable. Physicians’ attitudes against CPGs were found to be a highly important factor in the use of CPGs. And it was also observed that physicians’ positive attitudes against CPGs affected the use of CPGs in a positive way while negative attitudes had negative effect on use of CPGs.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC)